2009
DOI: 10.3109/02656730903315815
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of stress (heat shock) proteins in gastrointestinal tract

Abstract: This review will focus on gastrointestinal mucosal protection against cytotoxic agents and cellular stress mainly from the viewpoint of expression and function of heat shock proteins, in their role of 'molecular chaperones', as internal cytoprotectants. Also, recently identified target molecules of heat shock protein in damaged gastric mucosal cells are introduced. Elucidation of such stress-responses and repairing process of damaged protein by heat shock proteins in the gastrointestinal mucosa may provide a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Different HSPs control cytoprotection in each organ [8]. HSP70 contributes to mucosal protection in colon [14,15] and small intestine [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different HSPs control cytoprotection in each organ [8]. HSP70 contributes to mucosal protection in colon [14,15] and small intestine [16].…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock proteins (HSPs) have important functions in response to stress-related events in a variety of systems, including digestive organs [8,9]. In dextran sulfate sodium-induced colitis, an animal model of inflammatory bowel disease, mRNA expression of TNF-α, IL-1β and IL-6 in colonic tissue was inhibited in transgenic mice expressing HSP70 [10], and HSP70-dependent inhibition of NF-ĸB was the speculated mechanism to suppress inflammatory cytokines expression [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although HSP90 is a molecular chaperone that is ubiquitously expressed in living cells and plays an important role in cell growth and differentiation, no precise research has been performed to clarify the functional role of HSP90 in the intestinal mucosal cells. Since it has been reported that important HSP is different in each organ or each pathogenesis in view of cytoprotection, to elucidate the cytoprotective ability of each HSP is important for application of chaperone-inducing therapy to disease therapy [10,18]. These backgrounds allow us to study the cytoprotective function of HSP90-overexpressing small intestinal epithelial cells against oxidative stress and NSAIDs-induced cell damage.…”
Section: Introductionmentioning
confidence: 98%
“…The major inducible HSP, HSP70, is highly expressed within the mammalian gastrointestinal epithelia, where it has been shown to have a protective role against a range of cytotoxic agents (Nakamura et al, 1991;Oyake et al, 2006). Similarly, HSP60 and 90 and the small molecular weight HSP 25 have been reported to have gastrointestinal cytoprotective functions (Otaka et al, 2009;Tanaka and Mizushima, 2009). In their capacity as chaperones, HSPs also have a significant role in the mediation of immune responses (Robert, 2003;Srivastava, 2002).…”
Section: Inflammatory Bowel Disease (Ibd) That Includesmentioning
confidence: 99%
“…Hsp70 is regarded as having a major cytoprotective function in intestinal epithelial cells (Mizushima, 2010;Otaka et al, 2009). Biopsies from patients with IBD have shown enhanced intestinal expression of HSP70 (Ludwig et al, 1999).…”
Section: Inflammatory Bowel Disease (Ibd) That Includesmentioning
confidence: 99%